PENGARUH PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS (ZEA MAYS SACCHARATA STURT.) - Fadli, Mohamad; Fathillah, S. Syarief; Siahaan, Ferry Horison (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2020)
This study goal was to determine the effects of empty palm fruit bunch compost on the growth and yield of sweet corn (Zea mays Saccharata sturt). This research conducted in housing a palm oil plantation by PT Jaya Mandiri Sukses Kulim Estate (Eagle High Plantation) in perian village Muara Muntai, District Kutai Kartanegara Regency, East Kalimantan on ± 47 m above sea level, these research does at May 2019 until August 2019. This research used Randomized Complete Block Design (RCBD) with single factor (empty oil palm fruit bunches compost) and repeated five times. The studied factors were k0 = without compost (control), k1 = 6 t ha-1 (1,68 kg plot-1), k2 = 12 t ha-1 (3,36 kg plot-1), k3 = 18 t ha-1 (5,04 kg plot-1) and k4 = 24 t ha-1 (6,72 kg plot-1). The results showed that the treatment on oil palm empty fruit bunches had no significant effect on leaves aged average that is 21 days after planting, the length of cobs with out corn skinin 75 days after planting, but significantly effected on plant height 21 days after planting 42 days after planting and 75 days after planting, leaves aged average that is 42 days after planting and 75 days after planting, appearance time of male flowers, cob weight of each plot and yield per hectare (t ha-1). The lowes weight yield per hectare in the k0 treatment everage is 10,14 t ha-1 and hinghest result on k3 treatment everage is 17,21 t ha-1.